Application of the theory of promotional function in the civil procedural rules of brazilian Law as a substrate of the Democratic State of Law - Valverde Santanna, Héctor (2020)
The objective of this article is to analyze the applicability of the theory of the promotional function of law in the rules of Civil Procedural Law, observing the functionalist theory demonstrated by Norberto Bobbio, and its possible application in legal relations, mainly focused on Procedural Law, after the Code's validity. Civil Procedure Law 2015, due to the observation of the social control inherent to the legal system. It questions whether the use of premium sanctions for the interpretation and application of the rules contributes to the effective resolution of conflicts of interest after the new Civil Procedure Code of 2015 is in force? Based on a qualitative approach, after the diagnosis, it was possible to notice that the new Code of Civil Procedure has provisions that portray the premium sanctions and, although there is not a wide discussion and application of this sanctioning modality, it is an important tool for the interpretation of the rules of Civil Procedural Law.